STEAM EXPLOSION AS A PRE-TREATMENT METHOD FOR BIO-REFINED HYBRID ASPEN LIGNOCELLULOSE (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
Steam explosion (SE) is a well renowned pre-treatment method used for bio-refined material synthesis due to its simplicity in machinery and efficiency in resource and energy use in creation of high-value products. Used for separation of lignocellulose originated from wood and other sources, current research in wood-based lignocellulose has mainly focused in separation of wood fractions from commonly grown tree species. Scientific studies are needed for better understanding of common tree species to generate new possible products, e.g., bio-based composite materials. Commercially grown hybrid aspen (Populus tremuloides x Populus tremula) was pre-treated by SE to obtain a nano-level structured cellulose and lignin for bio-based composite materials. The results present a yield of extracted cellulose and lignin depending on SE conditions (severity factor) and subsequent water/alkaline extraction. Extractions have been executed with and without heat treatment. The research reveals a positive correlation between the yield of extracted lignin and SE severity factor, and a negative correlation for SE cellulose. The study concludes that SE hybrid aspen is proving to be a promising source for extraction of cellulose and lignin for bio-based composite materials.